(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Depression is the most often encountered in the world of mental illness. In adulthood these mental disorders do not understand as people do not want to share their mental illness with health care providers, they are fearful of receiving approval from the physician. The community people in the last century did not accept the existence of mental illness to the children. Nowadays some studies can provide evidence of mental illness and treatment, or the medical field is also evolving so that people believe disease and death rates. Earlier studies show that depression is prevalent in adolescents (10% to 60%). The mood disorder (depressive mood) may inform lows all around, people may go to sadness in this condition, and in a severe case, people may end their lives. A person may suffer for a long period in a situation in which he or she feels sad and does not participate in social, personal, professional life. In all life situations, the person feels low and does not feel pleasure in everyday life, so if the individual can feel these things in their life so that they consider depression. 3 influence of depression mood which is unusual at a particular age. This can lead to negative effects on a friend, social, and family relationship. 4 most suicide and suicidal behavior can lead to major depressive disorders. Younger depression can lead to chronic waxing and increased risk of major depression in adulthood. Some studies can indicate that depression may occur early in adulthood as opposed to people’s past lives.